Laparoscopic surgery for the treatment of gastrointestinal stromal tumors: Experience from Da Nang Hospital - Thoi, Dang Van; Hoang, Nguyen (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. Surgical resection with negative margins remains the cornerstone of curative treatment. Laparoscopic surgery has increasingly been adopted because of its safety and favorable perioperative outcomes. This study aimed to describe the clinical and paraclinical characteristics of GIST and to evaluate the early outcomes of laparoscopic surgery for GIST treatment. Methods: A cross-sectional descriptive study was conducted in 48 patients with pathologically confirmed gastrointestinal stromal tumors who underwent laparoscopic surgery at Da Nang Hospital from January 2022 to August 2023. Results: The mean age was 52.2 years, and the female-to-male ratio was 1.2:1. The stomach was the most common tumor location (54.2%), followed by the small intestine (27.1%). Abdominal pain was the most frequent presenting symptom (75.0%). Tumor detection rates were 77.3% by ultrasonography and 97.9% by computed tomography. The mean tumor size was 6.21 cm, and spindle-cell morphology accounted for 91.7% of cases. Laparoscopic surgery was completed successfully in 89.6% of patients, whereas 10.4% required conversion to open surgery. No intraoperative complications were recorded. The mean postoperative hospital stay was 6.1 days, and postoperative complications occurred in 4.2% of patients, all of which were mild surgical site infections. Conclusion: GISTs often present with non-specific clinical manifestations. Diagnosis should be based on a combination of imaging and histopathological evaluation, especially computed tomography and pathological examination. Laparoscopic surgery is a safe and effective treatment option for GIST and is associated with favorable early postoperative outcomes.